Analisis Pendekatan Trust Politic Korea Selatan dalam Penyelesaian Hambatan Reunifikasi di Semenanjung Korea - Fitrah, Elpeni; Ramadhani, Zakie Andiko (Insignia: Journal of International Relations, 2018)
This research investigates on South Korea trust politic approach under Park Geun Hye administration to handle the challenges of Korean reunification in Korean Peninsula based constructivism perspective. There are third challenges that faced by South Korea within Korean reunification which is international community believed on these challenges. Those challenges are the differences of ideology and system between South and North Korea, South Korea and United States of America military provocation, and North Korea’s nuclear weapon program. The type of this research is qualitative research that used secondary data by desk research approach and also using explanation methods to analyse the topic. Based on the result of this research, by using constructivism perspective those problems are not relevan more as barrier for Korean reunification in Korean peninsula. Today, the main problem to Korean reunification is what researcher called with “trust deficit” and identity changed. So that’s why South Korea used this kind approach where a structure of mistrust and confrontation is replaced by that of trust and cooperation. This structure changing is hoped to increase the possibility of reunification in Korean Peninsula between South and North Korea in the future.